Making it work ; Fighting fumes ; National treasures [videorecording] - Lazaro, Cheche (The Probe Team, 1994)
Documents unleaded gasoline putting a stop to air pollution, G.S.I.S. 34 million dollars overseas investments and the indigenous artistic culture like Ambahan, Basal and Kudyapi.